2016
DOI: 10.4172/pharmaceutical-sciences.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Total Polyphenols Extraction from Vigna angularis and Their Antioxidant Activities

Abstract: Zhang and Wang: Total Polyphenols from Vigna angularis and their EffectsVigna angularis, also called adzuki bean, a member of the family Fabaceae, has long been cultivated in Asian countries. This legume has received considerable attention owing to the presence of polyphenols. The optimal extraction conditions for total polyphenols from V. angularis and their antioxidant activities were investigated in this study. Ultrasound-assisted extraction was used to optimize the extraction of total polyphenols from V. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Bound phenolics need to be hydrolyzed with 2 mol/L NaOH and 12 mol/L HCl before further extraction (Aguilera et al., ; Ross, Beta, & Arntfield, ; Treviño‐Mejía, Luna‐Vital, Gaytán‐Martínez, Mendoza, & Loarca‐Piña, ). In addition, numerous studies have reported that the optimization of processing parameters plays a vital role in obtaining maximal polyphenols (Ghafoor, Choi, Jeon, & Jo, ; Jovanovic et al., ; Mourtzinos et al., ; Paleologou, Vasiliou, Grigorakis, & Makris, ; Wong, Li, Li, Razmovski‐Naumovski, & Chan, ; Zhang & Wang, ). However, few studies have systematically optimized the extraction conditions of common bean polyphenols.…”
Section: Extraction Separation and Identification Methodsmentioning
confidence: 99%
“…Bound phenolics need to be hydrolyzed with 2 mol/L NaOH and 12 mol/L HCl before further extraction (Aguilera et al., ; Ross, Beta, & Arntfield, ; Treviño‐Mejía, Luna‐Vital, Gaytán‐Martínez, Mendoza, & Loarca‐Piña, ). In addition, numerous studies have reported that the optimization of processing parameters plays a vital role in obtaining maximal polyphenols (Ghafoor, Choi, Jeon, & Jo, ; Jovanovic et al., ; Mourtzinos et al., ; Paleologou, Vasiliou, Grigorakis, & Makris, ; Wong, Li, Li, Razmovski‐Naumovski, & Chan, ; Zhang & Wang, ). However, few studies have systematically optimized the extraction conditions of common bean polyphenols.…”
Section: Extraction Separation and Identification Methodsmentioning
confidence: 99%
“…In a recent study (Zhang and Wang, 2016) aimed at optimization of TPC extraction from Vigna angularis, it was found that the optimal ethanol concentration for obtaining extracts was 40% in all the samples tested, Table 3. Box-Behnken experimental design based on independent variables (A, B and C) and experimental and predicted results of the TPC.…”
Section: Key Factors Affecting the Ultrasound-assisted Extraction Of mentioning
confidence: 99%
“…Hayta and İşçimen (2017) obtained the highest extraction yield of antioxidant compounds from chickpeas at 25°C, water solvent 0.40 w/v, 36.16% amplitude (power), and 20.17 min of HPU treatment. H. H. Zhang and Wang (2016) found that water + ethanol (40%) solvent (1:20 w/v ratio) at 25°C for 30 min with three rounds of extraction treatment represented the optimal conditions for maximizing the polyphenol extraction from red beans ( Vigna angularis ). Moreover, Miano et al.…”
Section: Facilitating Emerging Technologies For the Removal Of Unwant...mentioning
confidence: 99%
“…Hayta and İşçimen (2017) obtained the highest extraction yield of antioxidant compounds from chickpeas at 25 • C, water solvent 0.40 w/v, 36.16% amplitude (power), and 20.17 min of HPU treatment. H. H. Zhang and Wang (2016) found that water + ethanol (40%) solvent (1:20 w/v ratio) at 25 • C for 30 min with three rounds of extraction treatment represented the optimal conditions for maximizing the polyphenol extraction from red beans (Vigna angularis). Moreover, Miano et al (2019) claimed that employing this technology (25 • C, water, 25 kHz, 41 W/L, 300 min) for the hydration of lupine seeds before alkaloid extraction improved the removal yield of these ANFs by up to 21% compared to that from conventional hydration.…”
Section: 6mentioning
confidence: 99%